La responsabilidad compartida de los residuos posconsumo en el combate contra la contaminación transfronteriza - Efing, Antônio Carlos; Gomes Bergstein, Lais (Pontificia Universidad Católica del Perú, 2014)
This study analyzes the impact of the establishment of shared responsibility for post-consumer waste, as an instrument in the fight against environmental degradation, in the Brazilian legal system. it has as its premise that the increment of sustainability levels is essential, especially in the context of postmodernism, which is marked by mass consumption, extensive use of natural resources and the spreading of risks. Notably, consumer societies contribute enormously to the spread of this type of pollution, because they produce a profusion of consumer goods and, on the other hand, do not administer the post-consumer waste with the same efficiency. therefore, the proper management of product chain and life cycle waste is one of the greatest challenges to environmental preservation, especially in the case of the transportation of contaminants via natural forces, resulting in the so called transboundary pollution. the study found that only integrated actions among countries can lead to the preservation of an ecologically balanced environment to present and future generations. indeed, international cooperation is crucial to battle transboundary pollution, as well as to promote the establishment of legal systems which are compatible with the idea of sustainability. Furthermore, the study made it possible to conclude that shared responsibility, comprising introducing consumer’s active participation in reverse logistics, is fundamental to the achievement of the desired levels of sustainability. the present study was based on the deductive scientific method and predominantly relied on bibliographical resources.

Este estudio analiza el impacto de la institución de la responsabilidad compartida de los residuos posconsumo en la legislación brasileña, como un instrumento de combate contra la degradación ambiental. Parte de la premisa de que la elevación de los estándares de sustentabilidad en las sociedades es de suma importancia, especialmente en el contexto de la posmodenidad, que es marcada por el consumo masivo, la amplia utilización de recursos naturales y la propagación de los riesgos. en particular, las sociedades de consumo contribuyen enormemente con la propagación de este tipo de contaminación, pues producen bienes de consumo en abundancia, y, por otra parte, no administran los residuos del posconsumo con la misma eficiencia. Por lo tanto, la adecuada gestión de los residuos provenidos de la cadena productiva y del ciclo de vida de los productos es uno de los grandes desafíos para la preservación ambiental, especialmente en relación al transporte de agentes contaminantes por medio de fenómenos naturales, dando lugar a la llamada contaminación transfronteriza. el estudio constató que solamente acciones integradas entre los países puede conducir al mantenimiento del medio ambiente ecológicamente equilibrado para las presentes y futuras generaciones. en efecto, la cooperación internacional, además de promover el establecimiento de sistemas jurídicos compatibles con el estándar de sustentabilidad, es apremiante para combatir la contaminación transfronteriza. Asimismo, se concluyó que el compartimiento de responsabilidades, incluso imponiéndose la participación activa del consumidor en la realización de la logística inversa, es fundamental para el logro de los niveles deseados de sustentabilidad. El presente estudio se basa en el método científico deductivo y se realizó eminentemente la investigación bibliográfica.
Shared responsibility for post-consumer waste in the fight against transboundary pollution
Keywords: Law; Solid Waste; Shared Responsibility; Consumption; Sustainability; Residuos Sólidos; Responsabilidad Compartida; Consumo; Sustentabilidad; https://purl.org/pe-repo/ocde/ford#5.05.00